Radio Relics in Clusters of Galaxies: A unique case of Abell 548b - Tsarevsky, G.; Feretti, L.; Andernach, H.; Bacchi, M.; Slee, O.B.; Giovannini, G.; Govoni, F. (Известия Крымской астрофизической обсерватории, 2007)
Currently about 30 clusters of galaxies are known to have diffuse radio sources (so-called relics), but detailed studies are available for only a few. A548b, a rich and X-ray bright cluster of galaxies, is one of only three clusters (together with A3376 and A3667) known to contain two relics. From our investigation based on multi-wavelength ATCA and VLA observations, we found that both relics (A and B), located on the same side of the cluster’s center, show similar flux, extent, shape, high level of polarization and very steep spectral index. We conclude that these sources are likely related to the merger activity in the cluster. We have also possibly detected a centrally projected third relic (C). If confirmed, it would make A548b a unique triple-relic cluster.